2000
DOI: 10.1016/s0168-9452(99)00178-8
|View full text |Cite
|
Sign up to set email alerts
|

Xanthone biosynthesis and accumulation in calli and suspended cells of Hypericum androsaemum

Abstract: Calli and suspended cells of Hypericum androsaemum accumulated high levels of 1,3,5,6 and 1,3,6,7 oxygenated xanthones. The major compounds include simple oxygenated xanthones or derivatives with prenyl, pyran or methoxyl groups, four of them being new natural compounds. A hypothetical biosynthetic scheme is proposed based on the isolated compounds and statistical analysis. Xanthone accumulation was influenced greatly by medium factors, namely hormone supplementation. Calli grown with 4.5 mM a-naphtaleneacetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 28 publications
2
31
0
1
Order By: Relevance
“…Later, Ishiguro et al (1995) isolated prenylated xanthones and their cyclization products from the cell cultures of the same species. The accumulation of high levels of tetrahydroxyxanthones in calli and suspended cell cultures of H.androsaemum, dependent on hormone supplementation, and H. perforatum was reported by Dias et al (2000Dias et al ( , 2001. El-Mawla (2005) identified 1,7-dihydroxanthone, 1,3,7-trihydroxanthone and three tetrahydroxyxanthones in cell cultures of H. gnidioides grown in Gamborǵs B5 medium in the dark.…”
Section: Discussionmentioning
confidence: 93%
“…Later, Ishiguro et al (1995) isolated prenylated xanthones and their cyclization products from the cell cultures of the same species. The accumulation of high levels of tetrahydroxyxanthones in calli and suspended cell cultures of H.androsaemum, dependent on hormone supplementation, and H. perforatum was reported by Dias et al (2000Dias et al ( , 2001. El-Mawla (2005) identified 1,7-dihydroxanthone, 1,3,7-trihydroxanthone and three tetrahydroxyxanthones in cell cultures of H. gnidioides grown in Gamborǵs B5 medium in the dark.…”
Section: Discussionmentioning
confidence: 93%
“…Though naphtodianthrones and acyl-phloroglucinols represent the best investigated groups of metabolites in H. perforatum, there is still an increased demand for further research on flavonoids and xanthones as pharmacologically active compounds (Fotie and Bohle 2006;Nahrstedt and Butterweck 2010). In this view, several studies demonstrated the potential of Hypericum in vitro cultures to accumulate xanthones and their production can be manipulated by the culture type (Pasqua et al 2003), hormonal supplementation (Dias et al 2000), genetic transformation (Tusevski et al 2013) and elicitation (Conceição et al 2006;Franklin et al 2009;Tocci et al 2011). Among the studies for elicitation of H. perforatum cells, Conceição et al (2006) reported strong enhancement of xanthone accumulation upon treatments with Colletotrichum gloeosporioides, methyl jasmonate and salicylic acid.…”
Section: Introductionmentioning
confidence: 96%
“…Hypericum is a genus of about 400 species, some of which have been used as traditional medicinal plants for hundred of years due to their wound-healing, bactericide, anti-inflammatory, diuretic and sedative properties (Dias et al 2000). For example, extracts of Hypericum perforatum L. are widely used in Europe as a drug for the treatment of depression (Patocka 2003).…”
Section: Introductionmentioning
confidence: 99%